(untitled) (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The article reveals the opportunities of social media usage in social work with young people with special needs. The research allowed to describe the usage of different social media according to the main tasks of such organizations. The perception peculiarities of young people with hearing disorders were analysed based on the nature of the defection, its treatment and the level of person’s hearing perception. The results of the research show that such kinds of social media as social networks, content hosting, and online forums are used to perform specific tasks in the practice of social work with this specific category of clients. Depending on the main purposes of NGO such taskes may include communication on different levels, individual and group counseling, supervision elements, integration of rehabilitation tools in an accessible for young people form on the web. As a result of the research the model of social media usage in appliance with the main tasks of these NGO has been introduced.